2022
DOI: 10.1177/08862605221117548
|View full text |Cite
|
Sign up to set email alerts
|

Safeguarding in Church: Children and Young People’s Perceptions of Safety in Religious and Other Faith-Based Settings

Abstract: Organizations that interact with children and young people have a duty of care to ensure the safety of those children and young people from any manner of abuse, particularly from child sexual abuse. Faith-based (“religious”) organizations are of particular interest due to the number of victims/survivors speaking out about their experiences of grooming, child sexual abuse, and other forms of harm in religious organizations. Focusing on addressing the risks and improving safeguarding efforts, prevention activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…For example, the empirical literature shows that fear of violence (Collins, 2001; De Wet et al, 2018; Fabiansson, 2007; M. R. Hughes et al, 2015; Russell et al, 2023; Zuberi, 2018) and the presence of unfriendly people or criminals (Johansson et al, 2012; Nayak, 2003) threaten youths’ safety and constrain their exploration of the community. Further, consistent with the discourse, current research shows that environmental and public safety factors such as poor street lighting, litter, poor road traffic features, and low police patrols are safety concerns in urban communities (Carver et al, 2009; Doyle et al, 2016; Johansson et al, 2012; Yang, Liller, Coulter, et al, 2022; Yang, Liller, Tyson, et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, the empirical literature shows that fear of violence (Collins, 2001; De Wet et al, 2018; Fabiansson, 2007; M. R. Hughes et al, 2015; Russell et al, 2023; Zuberi, 2018) and the presence of unfriendly people or criminals (Johansson et al, 2012; Nayak, 2003) threaten youths’ safety and constrain their exploration of the community. Further, consistent with the discourse, current research shows that environmental and public safety factors such as poor street lighting, litter, poor road traffic features, and low police patrols are safety concerns in urban communities (Carver et al, 2009; Doyle et al, 2016; Johansson et al, 2012; Yang, Liller, Coulter, et al, 2022; Yang, Liller, Tyson, et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Current research with youth has identified themes on what makes young people feel safe or unsafe in the community. These themes relate to features of the physical environment, road traffic system features, public safety practices, and social cohesion factors (Carver et al, 2009; De Wet et al, 2018; Johansson et al, 2012; Russell et al, 2023; Slaato et al, 2023; Yang, Liller, Tyson, et al, 2022). Regarding the physical environment of the community, research shows that young people perceive cleanliness, functional lampposts, and fire hydrants among others as safety enhancing whereas they perceive an environment filled with litter and trash and dysfunctional lampposts and fire hydrants as unsafe (Yang, Liller, Coulter, et al, 2022; Yang, Liller, Tyson, et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations